Keeping up appearances: agarwood grades and quality - Mohamed, Rozi; Lee, Shiou Yih (Springer, 2016)
Agarwood has many grades and goes by countless different names in both the sourcing and consuming countries. The different grades and classes of agarwood result from long-standing grading practices adopted by the people of each country. No standard method is available partly due to the intricacy during the hierarchical process of selling and buying. The foremost reason is the appearance of the traded agarwood itself, which can come in many forms from raw, such as chips, blocks, and flakes, to finished products such as oil, incenses, perfumes, accessories, and carvings. Agarwood in raw forms is of mixed quality; thus, the price and grade depend on this blended appearance. As the product is passed down from collectors to various levels of traders and finally to the buyers, the grade can be readjusted and the price inflated or understated depending on the interest. Therefore, buyers, traders, and collectors heavily rely upon time-honored trust when concluding a business deal. Authorities have not found the formula to standardize the grading system of agarwood trade, and this leads to the lack of coordination and regulation at international level. Nevertheless, several sourcing and consuming countries have made the effort to grade their agarwood according to their own local market, which can be used as a benchmark in formulating a more contemporary method that could be acceptable to all countries.